2018
DOI: 10.14742/ajet.3237
|View full text |Cite
|
Sign up to set email alerts
|

A tale of two MOOCs: How student motivation and participation predict learning outcomes in different MOOCs

Abstract: Recent scholarly discussions about massive open online courses (MOOCs) highlight pedagogical and practical issues that separate MOOCs from other learning settings, especially how theories of learning translate to MOOC students' motivation, participation, and performance. What is missing from these discussions is the purpose of the MOOC. We report a comparative study of two MOOCs that differ in educational purpose, but are similar in design. Our sample consisted of 983 students in a professional development MOO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 24 publications
(47 reference statements)
3
33
0
1
Order By: Relevance
“…Therefore Onah et al (2015) suggested that student motivation might be more important in predicting success. Similarly, Brooker, Corrin, de Barba, Lodge and Kennedy (2018) reported that in a professional development MOOC (which would be consistent with our situation), professional development motivation contributed to the final grade, and their review of the literature emphasised the importance of motivation in student participation and performance. Although we did not measure motivation, our results lead us to conclude that motivation to complete the course is likely to be a confounding factor, influencing both commitment to participation in discussion forums and the outcomes of grades and course completion.…”
Section: Other Experiencesupporting
confidence: 81%
“…Therefore Onah et al (2015) suggested that student motivation might be more important in predicting success. Similarly, Brooker, Corrin, de Barba, Lodge and Kennedy (2018) reported that in a professional development MOOC (which would be consistent with our situation), professional development motivation contributed to the final grade, and their review of the literature emphasised the importance of motivation in student participation and performance. Although we did not measure motivation, our results lead us to conclude that motivation to complete the course is likely to be a confounding factor, influencing both commitment to participation in discussion forums and the outcomes of grades and course completion.…”
Section: Other Experiencesupporting
confidence: 81%
“…Therefore Onah et al (2015) suggested that student motivation might be more important in predicting success. Similarly, Brooker, Corrin, de Barba, Lodge and Kennedy (2018) reported that in a professional development MOOC (which would be consistent with our situation), professional development motivation contributed to the final grade, and their review of the literature emphasised the importance of motivation in student participation and performance. Although we did not measure motivation, our results lead us to conclude that motivation to complete the course is likely to be a confounding factor, influencing both commitment to participation in discussion forums and the outcomes of grades and course completion.…”
Section: Other Experiencesupporting
confidence: 81%
“…Therefore, the emergence of this factor might stem from the features of course design. A number of studies have also underlined the importance of interaction among students as an ingredient for success in the MOOC (Brooker et al, 2018;İbicioğlu & Antalyalı, 2005;Koutropoulos & Hogue, 2012;Loizzo & Ertmer, 2015;Soong et al, 2001). Consequently, designing online courses which can enhance interaction among participants and offer collaborative activities can promote participants' achievement in the MOOC.…”
Section: Discussion Of Findingsmentioning
confidence: 99%